The Role of Old and New Media in Supporting the Saudi Audiences Family Values - Comparative and Field Study - Filimban, Anwaar Abdullah (Journal of Humanities & Social Sciences, 2022)
The study aimed to monitor the role of the Traditional and New media in influencing the dimensions of the family values system of the Saudi public by identifying the values that the Saudi families believe in, and pinpointing the extent of the media support to the Saudi family values to rank the values according to the most supportive by the media. Also, the study aims to monitor Saudi families' view exposure and their patterns of view of the Traditional and New media. The study used the descriptive and comparative approach by surveying the respondents' opinions about the Media's role in supporting their family values and comparing the results at the level of Traditional and New media in terms of use, exposure pattern within the framework of the Theory of Value Media Determinism. The study used an electronic questionnaire tool to collect data from the study sample, which consisted of (400) individuals from the Saudi community to study 9 values dimensions. The study reached many significant results. The most important values ​​most supported by the media are the values ​​in the health dimension with arithmetic mean (3.744), then the humanity dimension with arithmetic mean (3.563), then the social dimension with arithmetic mean (3.441). In contrast, the least supported values ​​from the media are the values ​​in the temporal dimension with arithmetic mean (2.927). The study found a set of recommendations, some of it are for media, such as the necessity of publishing the cultural value programs until the extent entrenches immunity in the families, and the other recommendations are for families and schools, the most important of which is the need to preserve the Saudi civilizational dimension, enhance cultural identity, teach family values, and train children on critical and analytical skills for media exposure, and other recommendations.
Keywords: Traditional media; New media; Family Values; Value Media Determinism Theory; Saudi Community